1993
DOI: 10.1002/path.1711700409
|View full text |Cite
|
Sign up to set email alerts
|

P53 overexpression and Epstein‐Barr virus infection in undifferentiated and squamous cell nasopharyngeal carcinomas

Abstract: We have analysed 22 nasopharyngeal carcinomas (NPCs) for expression of the small nuclear Epstein-Barr virus (EBV)-encoded RNAs (EBERs) and for immunohistologically detectable overexpression of p53. In situ hybridization demonstrated expression of the EBERs in 13 undifferentiated NPCs while nine squamous cell NPCs were EBER-negative. These results therefore confirm our previous DNA-DNA in situ hybridization studies and demonstrate that in the nasopharynx EBV is exclusively associated with undifferentiated but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
57
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 20 publications
9
57
0
1
Order By: Relevance
“…Immunohistochemistry for p53 expression showed that many of the malignant epithelial cells in the tumours expressed readily detectable levels of nuclear p53 (summarized in Table 2). Again this was consistent with previous reports (Niedobitek et al, 1993;Sheu et al, 1995;Murono et al, 1999).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Immunohistochemistry for p53 expression showed that many of the malignant epithelial cells in the tumours expressed readily detectable levels of nuclear p53 (summarized in Table 2). Again this was consistent with previous reports (Niedobitek et al, 1993;Sheu et al, 1995;Murono et al, 1999).…”
supporting
confidence: 94%
“…Characteristically these undi erentiated tumours include a signi®cant in®ltration of T lymphocytes (reviewed in Niedobitek et al, 1996), up to 60% fail to express the tumour suppressor protein p16 INK4A (Lo et al, 1995(Lo et al, , 1996Sun et al, 1995;Gulley et al, 1998) and ± unlike most human tumours ± nearly 100% are wild type for the p53 tumour suppressor gene (E ert et al, 1992;Sun et al, 1992;Lo et al, 1992;Spruck et al, 1992). Paradoxically and in contrast to most normal tissues, although only wild type p53 alleles are present, in most NPC su cient p53 is expressed for it to be detectable by immunohistochemistry (Niedobitek et al, 1993;Sheu et al, 1995;Murono et al, 1999). Since these cells are rapidly proliferating, the p53 protein is assumed to be inactivated.…”
mentioning
confidence: 99%
“…LMP1 has also been suggested to induce p53 expression in resting human B cells through NF-kB induction, resulting in the accumulation of p53 protein and elevated levels of p53 detected in NPC (Niedobitek et al, 1993;Chen and Cooper, 1996). To detect effects of LMP1 expression on p53 protein levels, immunoblot analysis for p53 in whole-cell extracts from lymphomas in transgenic and control mice revealed consistently high levels of p53 in all LMP1 transgenic lymphomas (L1-5), while spontaneous LMP1-negative counterparts demonstrated lower and variable levels of p53 (C1-3) (Figure 6b).…”
Section: Upregulation Of Traf1mentioning
confidence: 99%
“…This model system can also be used to evaluate the contribution of host cell genetic factors, such as tumour suppressor genes and activated cellular oncogenes, to the formation of tumours in SCID mice. We analysed expression of the p53 tumour suppressor gene and the anti-apoptotic bcl-2 gene in tumours produced by HaCaT LMP transfectants as overexpression of both genes has been implicated in the pathogenesis of NPC (Niedobitek et al, 1993;Lu et al, 1993). Tumour sections were negative for bcl-2, indicating that bcl-2 does not play a role in tumour development.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation and/or overexpression of the p53 tumour suppressor gene is a frequent event in many types of human cancer (Hollstein et al, 1991) including NPC (Niedobitek et al, 1993). Mutation resulting in overexpression of the HaCaT p53 gene has been reported (Lehman et al, 1993), and raises the possibility that this property of the HaCaT cell line is required to allow expression of LMP oncogenicity.…”
Section: Contribution Of Cellular Genes To Tumorigenicitymentioning
confidence: 99%